Analysis of genetic polymorphisms in the intron 9–10/exon 10 region of the BRCA1 gene in a population sample of dogs with mammary cancer from Uruguay - Decuadro, Alicia; Sosa, Micaela; García, Federico; Balemian, Nariné; Montenegro, María del Carmen; Llambí, Silvia (Universidad del Zulia p-ISSN 0798-2259; e-ISSN 2521-9715; l-ISSN 2477-944X, 2025)
This study involved clinical and genetic analysis of 15 female dogs with mammary tumors. Fourteen healthy female dogs were used as controls, and blood samples were collected from them for genetic analysis. Polymorphisms located in a splicing region of the largest exon of the BRCA1 gene were studied, both at the population and evolutionary level, in a population of female dogs with different histopathological types of mammary tumors. In the intron 9–10/exon 10 initiation region, two SNP–type polymorphisms are described: SNP1 and SNP2. The SNP1 produces a non–synonymous change with unknown effect on the coding protein. Selected animals underwent surgery, and samples were sent for histopathological analysis. Peripheral blood was also collected for DNA extraction. A region corresponding to intron 9–10/exon 10 of the BRCA1 gene (ENSCAFE00845051080) was amplified by endpoint PCR, with PCR results subsequently confirmed through agarose gel electrophoresis at 1%. PCR products were sequenced to study the polymorphisms identified within this region. No statistically significant differences were observed between the genotype frequencies in both populations (Chi2 0.33, P>0.5), indicating that SNP1 is not linked to mammary tumors in the studied animals. Regarding SNP2, the mutation was not identified in the studied groups (females with mammary tumors and controls), being monomorphic. Although this SNP2 is described in the Ensembl database, there are no genotyping data in reference populations. The phylogenetic analysis of the amplified intron 9–10/exon 10 revealed an evolutionary homology with Canis lupus familiaris, and a more distant relationship with other genera such as Vulpes and Nyctereutes within the Canidae family. It can be concluded that mutations in this splicing region of the largest exon of BRCA1 are not associated with the development of mammary tumors in canines within this group of animals. Se realizó el estudio clínico y genético en 15 perras con tumores de mama. El grupo control incluyó 14 perras sanas ...